SYNTHESIZING PD (II), RU (II) BENZONITRILE-PHENOTHIAZINE DERIVATIVE COMPLEXES AND INVESTIGATING THEIR ANTIBACTERIAL ACTIVITY AND REMOVAL OF SOME HEAVY METALS IN ENVIRONMENTAL SYSTEMS - G. Sh. Al-Obaidy; H. Kh. Kh. Al-Dulymi; M. A. Abed (مجلة الأنبار للعلوم الزراعية)
First, phenol thiazine is reacted with sodium metabisulphite, sodium cyanide, and 4-Formylbenzonitrile to yield the appropriate nitrile. In this study, 4-(cyano(10H-phenothiazin-10-yl)methyl)benzonitrile, a phenothiazine derivative, was synthesized. The stereoscopic shape of the complexes formed around the ionic centers was determined using spectroscopic and physical techniques, including elemental analysis, 1H-NMR and 13C- NMR spectra, FTIR, UV-Vis, metal content, and conductance measurements. After synthesizing the derivatives of the complexes the biological activity of the prepared ligand and its complexes was studied to estimate their potential antimicrobial activity. In general, tests show the ligand and its complexes having good activity against bacteria. The prepared ligand was used to remove heavy metals causing water pollution. Among the heavy elements studied were zinc, lead, and copper. The findings suggest that the prepared complexes may be used to lower concentrations of these elements in water and mitigate their impact on the environment.